Spatial behavior and habitat use in widely separated breeding and wintering distributions across three species of long‐distance migrant Phylloscopus warblers. Issue 11 (24th May 2019) - Lerche‐Jørgensen, Mathilde; Mallord, John W.; Willemoes, Mikkel; Orsman, Christopher J.; Roberts, Japheth T.; Skeen, Roger Q.; Eskildsen, Daniel P.; Salewski, Volker; Tøttrup, Anders P.; Thorup, Kasper
Abstract: Aim: To investigate the ecological relationship between breeding and wintering in specialist and generalist long‐distance migratory species, and the links between densities and range sizes. Location: Denmark, Senegal and Ghana. Methods: We use radio tracking to study spatial behavior and habitat use in three morphologically and ecologically similar and closely related Phylloscopus species on their widely separated breeding and wintering distributions. During wintering and breeding, willow warblers P. trochilus (winter: n = 9, breeding: n = 13), chiffchaffs P. collybita ( n = 11, n = 7), and wood warblers P. sibilatrix ( n = 17, n = 14) were tracked. Results: Willow warblers P. trochilus increased home range sizes in winter, whereas it was similar in chiffchaffs P. collybita and wood warblers P. sibilatrix, in both seasons. Home ranges overlapped more in winter than in the breeding season. In winter, home range overlap was similar among species but larger overlap during breeding was indicated for willow warblers. Tree cover was unrelated to home range size but significantly higher in breeding than in winter in all species. However, whereas willow warblers and wood warblers maintained some degree of tall tree cover inside their home ranges in winter, chiffchaffs changed from more than 80% to <1% tree cover, indicating a niche shift. Main conclusions: Individuals of all three species showed changes between breeding and wintering areas in spatial behavior and habitat availability, with larger overlap in winter. The differences in patterns were potentially related to being generalist (willow warbler) or specialist (chiffchaff and wood warbler). These ecological relationships are important for the conservation of migrants and for understanding the link between breeding and wintering distributions and ecology. Abstract : We use radio‐tracking to link spatial behaviour and habitat use in three morphologically and ecologically similar and closely related Phylloscopus species on their widely separated breeding and wintering distributions. Individuals of all three species showed changes between breeding and wintering areas in spatial behaviour and habitat availability, with larger overlap in winter and some differences in patterns between generalists and specialists.